THE INFLUENCE OF RELIGIOSITY ON SELF-CONTROL OF PRISONERS IN NARCOTICS CORRECTIONAL INSTITUTIONS CLASS IIA GUNUNG SINDUR - Putra Widyaningtyas, Muhammad Naufal Hisyami; Warih, Wido Cepaka (Journal of Management Small and Medium Enterprises (SMEs), 2025)
Prisoners with good self-control abilities tend to show positive behavior in prison, while prisoners who are less able to control themselves will experience negative impacts in the form of failure in undergoing the coaching program. The method used in this study is quantitative, with a simple random sample technique of 189 respondents. The data collection technique was carried out using a questionnaire. The results showed that there is an effect of religiosity on prisoners' self-control. The level of influence given by the religiosity variable on prisoners' self-control is 67.5%, while the remaining 32.5% is influenced by other variables not discussed in this study. From these results, it can be concluded that there is a significant influence with a unidirectional (positive) relationship between religiosity and the self-control of prisoners in the Class IIA Narcotics Prison Gunung Sindur. Keywords: Religiousity; Self-Control; Inmates